Etiology of bovine mastitis in and around Palampur in Himachal Pradesh - Nagal, K B; Sharma, Mandeep; Katoch, R C (The Indian Journal of Animal Sciences, 2012)
The spectrum of bacterial pathogens were isolated from cases of bovine mastitis over a period of 9 years. Of the 728 mastitic milk samples cultured 51.51 % yielded bacterial and Candida spp. involvement whilst one sample yielded Protatheca spp. (0.14%). The occurrence of mastitis due to Staphylococcus aureus was the highest (61.76%) followed by Streptococcus pyogenes (12.03%) and Staphylococcus epidermidis (2.4%). The other bacteria encountered were E. coli (5.61%), Corynebacterium spp. (4.01 %), Bacillus spp. (1.53%), Pasteurella multocitda (0.8%), Pseudomonas aerugiposa (0.53%), Nocardia asteroides (0.26%), Proteus spp. (0.26%) and Candida spp. (1.87%). The antibiotics effective in descending order were gentamicin, chloramphenicol, tetracyclines and nitrofuratoin.